Integrative molecular structure elucidation and construction of an extended metabolic pathway associated with an ancient innate immune response in COVID-19 patients - Sala, Samuele; Nitschke, Philipp; Masuda, Reika; Gray, Nicola; Lawler, Nathan G.; Wood, James M.; Buckler, Joshua N.; Berezhnoy, Georgy; Bolaños, Jose; Boughton, Berin A.; Lonati, Caterina; Rössler, Titus; et al. (Journal of proteome research, 2024)
We present compelling evidence for the existence of an extended innate viperin-dependent pathway, which provides crucial evidence for an adaptive response to viral agents, such as SARS-CoV-2. We show the in vivo biosynthesis of a family of novel endogenous cytosine metabolites with potential antiviral activities. Two-dimensional nuclear magnetic resonance (NMR) spectroscopy revealed a characteristic spin-system motif, indicating the presence of an extended panel of urinary metabolites during the acute viral replication phase. Mass spectrometry additionally enabled the characterization and quantification of the most abundant serum metabolites, showing the potential diagnostic value of the compounds for viral infections. In total, we unveiled ten nucleoside (cytosine- and uracil-based) analogue structures, eight of which were previously unknown in humans allowing us to propose a new extended viperin pathway for the innate production of antiviral compounds. The molecular structures of the nucleoside analogues and their correlation with an array of serum cytokines, including IFN-α2, IFN-γ, and IL-10, suggest an association with the viperin enzyme contributing to an ancient endogenous innate immune defense mechanism against viral infection.
Gesehen am 16.09.2024